Evidence syntheses to support decision-making related to the Covid-19 pandemic - Keitty Regina Cordeiro de Andrade; Viviane Karoline da Silva Carvalho; Roberta Borges Silva; Cézar D. Luquine Junior; Cecília Menezes Farinasso; Cintia de Freitas Oliveira; Fabiana Mascarenhas; Gabriel Antônio Rezende de Paula; Isabela Porto de Toledo; Marina Arruda Melo Marinho; Virginia Kagure Wachira; Alessandra de Sá Earp Siqueira; et al. (Universidade de São Paulo, 2024)
ABSTRACT The COVID-19 pandemic generated a large volume of scientific productions with different quality levels. The speed with which knowledge was produced and shared worldwide imposed on health management the challenge of seeking ways to identify the best available evidence to support its decisions. In response to this challenge, the Department of Science and Technology of the Brazilian Ministry of Health started offering a service to produce and provide scientific knowledge addressing priority public health issues in the pandemic scenario. Drug treatments, non-pharmacological measures, testing, reinfection and immunological response, immunization, pathophysiology, post-COVID syndrome and adverse events are among the topics covered. In this article, we discuss the strengths and lessons learned, as well as the challenges and perspectives that present a real example of how to offer the best scientific evidence in a timely manner in order to assist the decision-making process during a public health emergency.